Determinant Analysis of Macroeconomic Effect on Bank Stock Return Book 4 on the Indonesia Stock Exchange - Irwan Daud; Pardomuan Sihombing (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze macroeconomics on BOOK 4 Bank stock returns. This research uses the Vector Error Correction Model (VECM) method using monthly data on BOOK 4 Bank stock returns as the dependent variable and monthly inflation data, BI 7 days reverse repo interest rate. Rate, exchange rate, money supply, gross domestic product, foreign exchange reserves, and the fed funds rate, as independent variables, with a data time span from January 2016 to December 2020. The results show that in the short-term inflation, GDP, and foreign exchange reserves are variable. And the fed fund rate does not affect stock returns. The BI 7-day reverse repo rate and money supply variables have a significant positive effect, and the exchange rate has a significant negative effect on BOOK 4 bank stock returns. In the long-term inflation, the BI 7-day reverse repo rate, money supply, GDP, foreign exchange reserves, and the fed funds rate do not affect stock returns. Meanwhile, the exchange rate has a significant negative effect on BOOK 4 bank stock returns.